Вiomechanical rationale for the choice of surgical tactic for treatment of distal femur fractures consolidation disturbances - Golka, Grigoriy; Belostotsky, Anton (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to study stress-strain distribution in osteosynthesis model with non-union of distal femoral fracture and to define the most effective ways of injury fixation. Methods: finite element model of distal femur with different length are created, which is determined by distance (3 and 10 cm) from the top edge to the fracture line of lateral condyle. To fix the fracture used: blocked intramedullary rod, LCP-plate and 95° bladed plate. The area of contact between the fragments was 50 %. To load the appropriate models applied in the natural two-limb standing and flexion of knee joint with rotatory displacement. Results: it is revealed that for all model rotary load is critical in terms of stress in bone tissue, locking elements and structures in general and displacement of fragments of bones. In a case of fracture localization in the epiphyseal part of the femur, safer fixation of short distal fragment provides LCP-plate, so it should be used in such cases. Given the non-union location in the distal diaphyses of the femur bone stress are smallest and largest system stability «bone – fixation device» to load strains provides model with blocked intramedullar nail. Therefore, for fixation of fracture consolidation problems in the distal femur blocked nail is recommend. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">t<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">he obtained results allow to justify the method of surgical treatment of patients with impaired consolidation of the distal femur fracture, ie. to select fixation device depending on the injury level and the length of distal fragment.